PENCEGAHAN BULLYING PADA ANAK SEKOLAH DASAR DI SD N 1 MIPIRAN KECAMATAN PADAMARA KABUPATEN PURBALINGGA (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The role of Elementary Schools (SD) in preventing bullying is very important and involves several effective strategies and actions. Things that can be done are holding anti-violence programs, increasing supervision, providing appropriate sanctions, conducting campaigns through learning, involving parents, building student awareness, and developing prevention programs. The method used is socialization and mentoring for teachers to provide an effective model for preventing bullying in elementary school children. The results of this community service are that teachers understand and are able to interpret bullying prevention in elementary schools. In addition, other results are that the Principal and Class Teachers can design a bullying prevention policy in elementary schools.